2016
DOI: 10.18632/oncotarget.8741
|View full text |Cite
|
Sign up to set email alerts
|

EZH2-mediated repression of GSK-3β and TP53 promotes Wnt/β-catenin signaling-dependent cell expansion in cervical carcinoma

Abstract: Enhancer of zeste homolog 2 (EZH2), a catalytic core component of the Polycomb repressive complex 2 (PRC2), stimulates the silencing of target genes through histone H3 lysine 27 trimethylation (H3K27me3). Recent findings have indicated EZH2 is involved in the development and progression of various human cancers. However, the exact mechanism of EZH2 in the promotion of cervical cancer is largely unknown. Here, we show that EZH2 expression gradually increases during the progression of cervical cancer. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 59 publications
2
35
1
Order By: Relevance
“…Zhang et al found that lncRNA‐ANCR accelerated cell proliferation, migration, and invasion of osteosarcoma (OS) cells by downregulating p21 and p27 via interacting with EZH2 . It is noteworthy that EZH2 has been reported to downregulate the level of GSK‐3β gene expression through H3K27me3 in the GSK‐3β promoter . In our study, we found a significantly higher level of GSK‐3β levels in CRC tissues compared with adjacent normal tissues and cell lines, which was consistent with the previous studies .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Zhang et al found that lncRNA‐ANCR accelerated cell proliferation, migration, and invasion of osteosarcoma (OS) cells by downregulating p21 and p27 via interacting with EZH2 . It is noteworthy that EZH2 has been reported to downregulate the level of GSK‐3β gene expression through H3K27me3 in the GSK‐3β promoter . In our study, we found a significantly higher level of GSK‐3β levels in CRC tissues compared with adjacent normal tissues and cell lines, which was consistent with the previous studies .…”
Section: Discussionsupporting
confidence: 92%
“…20 It is noteworthy that EZH2 has been reported to downregulate the level of GSK-3β gene expression through H3K27me3 in the GSK-3β promoter. 11 In our study, we found a significantly higher level of GSK-3β levels in CRC tissues compared with adjacent normal tissues and cell lines, which was consistent with the previous studies. 5,21,22 In addition, we observed that GSK-3β mRNA and protein levels were markedly decreased due to lncRNA BDNF-AS overexpression in vitro.…”
Section: Lncrna Bdnf-as Repressed Gsk-3β Expression Via Ezh2-mediatsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, EZH2 is found to induce EMT and thus fibrogenesis in endometriosis, and there are signs to indicate that platelet aggregation in lesions may be responsible for EZH2 activation . Importantly, EZH2 may mediate the repression of GSK‐3β and TP53 and promote the activation of the Wnt/β‐catenin signaling pathway . The profibrogenic role of the Wnt/β‐catenin signaling pathway in endometriosis has recently been reported .…”
Section: Mutations Of Cancer Driver Genes In Endometriosis and Their mentioning
confidence: 99%
“…and promote the activation of the Wnt/β-catenin signaling pathway. 127 The profibrogenic role of the Wnt/β-catenin signaling pathway in endometriosis has recently been reported. 128 133,134 In addition, TET1, TET2, and TET3 expression is reported to be decreased.…”
Section: Tp53mentioning
confidence: 99%